Gold score athletics: talent detection model for track and field - van Keulen, G. E.; Werneck, F. Z.; Coelho, E. F.; Aguiar, C. M.; Miranda, L.; de Lima, J. R. P. (Revista Brasileira de Medicina do Esporte, 2023)
Introduction: Talent detection is a dynamic and multifactorial process that must start at school.